2018
DOI: 10.1080/10717544.2018.1477862
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-targeted design of bioresponsive prodrug with enhanced cellular uptake to achieve precise cancer therapy

Abstract: Chemical drug design based on the biochemical characteristics of cancer cells has become an important strategy for discovery of novel anticancer drugs to enhance the cancer targeting effects and biocompatibility, and decrease toxic side effects. Camptothecin (CPT) demonstrated strong anticancer activity in clinical trials but also notorious adverse effects. In this study, we presented a smart targeted delivery system (Biotin-ss-CPT) that consists of cancer-targeted moiety (biotin), a cleavable disulfide linker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The biotin-receptor is a well-known tumour-associated receptor that is overexpressed in many cancers, including those of the breast, lung, ovarian, and renal 7 , 8 . Biotin-receptor binds biotin ( 1 , Figure 1 ) with high affinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biotin-receptor is a well-known tumour-associated receptor that is overexpressed in many cancers, including those of the breast, lung, ovarian, and renal 7 , 8 . Biotin-receptor binds biotin ( 1 , Figure 1 ) with high affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Various biotin-conjugates (e.g. 2 and 3 , Figure 1 ) have been developed and tested in culture cells and animal models with successful results 7 , 9 , 10 . Utilising biotin as a “tumor-targeting ligand” is a promising method for designing tumour-specific conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…Drug delivery efficacy significantly depends on the cellular uptake of drugs. Effective uptake of drugs is a crucial issue for favorable treatment outcomes (Liang et al, 2018). Many studies have shown that RGD receptor a v b 3 integrin is overexpressed in cancer cells (Oe et al, 2014).…”
Section: Selective Uptake Of Rgdfc-se@sirna Nanoparticlesmentioning
confidence: 99%
“…Nano-sized particles are capable of working as pharmaceutical carriers for various delivery systems, orally, transdermally, or intravenously. Studies show that NPs have been tremendously used in the biomedical sector to treat diseases like diabetes [10][11][12] and cancer [13][14][15] . Among all the existing NPs, a polymer that makes good NPs is chitosan (CS) due to its special properties.…”
Section: Introductionmentioning
confidence: 99%